The Role of Industry Standards: An Overview of the Top Engineering Schools' Libraries. - Brian S. Mathews (Issues in Science and Technology Librarianship)
How important are industry standards to the academic library collection? This article seeks to provide a snapshot of the use, assistance with, relevance, and availability of standards within libraries supporting top ranked engineering programs. The study consists of three measurements: a review of web sites, an unobtrusive e-mail reference inquiry, and a survey of engineering subject specialists. The findings suggest that although standards are a valued resource, financial constraints, varied interest, and limited exposure contribute to their underutilization. [ABSTRACT FROM AUTHOR]